Dynamics of general and specially trained of women-weightlifters at the stage of specialized basic training - Viktor Slobodyanuk (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to determine the dynamics of the general and special training of women-weightlifters different groups weight categories for annual macrocycle at the stage of specialized basic training. Materials and Methods: indexes long jump, running 30 meters, push-ups, jumps on how Abalakova index and wrist strength athletes different schools of Ukraine. Results: found dynamic indicators of general and special training of women-weightlifters different groups weight categories at the stage of basic training six specialized schools in Ukraine. Conclusions: the results of the study provide an opportunity to consider certain indicators in planning differentiated training programs to improve the training process athletes for women-weightlifters at the stage of specialized basic training different groups weight categories in the annual macrocycle.